2011
DOI: 10.1080/01635581.2011.535960
|View full text |Cite
|
Sign up to set email alerts
|

Circulating 25-Hydroxyvitamin-D and Risk of Colorectal Adenomas and Hyperplastic Polyps

Abstract: Colorectal adenomas are clear precursors of cancer; hyperplastic polyps may also have malignant potential. An inverse association between circulating vitamin D metabolites and adenoma risk has been reported, but less is known about vitamin D and hyperplastic polyps. We conducted a case-control study of adenomas and hyperplastic polyps among 459 members of an integrated health plan evaluated via colonoscopy. Questionnaires provided information on colorectal polyp risk factors, and plasma samples were assayed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
(60 reference statements)
2
24
0
Order By: Relevance
“…Reduced SP risks were detected for individuals consuming the highest compared with the lowest intakes of calcium, fiber and folate, although only the latter was significant (RR, 0.65; 95% CI, 0.49-0.85) and all estimates had moderate heterogeneity. Vitamin D intake was not associated with SP risk (Figure 7), which is in agreement with another study measuring circulating 25-hydroxyvitamin D status 63 .…”
Section: Dietary Factorssupporting
confidence: 80%
See 1 more Smart Citation
“…Reduced SP risks were detected for individuals consuming the highest compared with the lowest intakes of calcium, fiber and folate, although only the latter was significant (RR, 0.65; 95% CI, 0.49-0.85) and all estimates had moderate heterogeneity. Vitamin D intake was not associated with SP risk (Figure 7), which is in agreement with another study measuring circulating 25-hydroxyvitamin D status 63 .…”
Section: Dietary Factorssupporting
confidence: 80%
“…Fifteen articles published on a range of dietary factors and SP risk 25,28,32,38,40,42,44,54,55,[63][64][65][66][67][68] , only one of which reported SSA/P risk separately 55 , as shown in Supplementary .…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Prior to colonoscopy, a sequential sample of individuals were invited to take part in a study of colorectal cancer screening markers (39, 40). All study protocols were approved by Institutional Review Boards at GH and the Fred Hutchinson Cancer Research Center (FHCRC).…”
Section: Methodsmentioning
confidence: 99%
“…These associations suggest that vitamin D deficiency might be related to the serrated pathway of CRC. Earlier studies have reported that vitamin D deficiency is not a risk factor for colorectal hyperplastic polyps25, but to our knowledge, little is known of the association between vitamin D deficiency and sessile and traditional serrated adenomas, which is an important subject for further investigation, since hyperplastic polyps are very common, and the risk of neoplastic progression has not been attributed to hyperplastic polyps but sessile and traditional serrated adenomas6.…”
Section: Discussionmentioning
confidence: 92%